Genetic polymorphism of MHC DRB3 (Major Histocompatibility Complex) of Bali cattle at Maiwa Breeding Center, South Sulawesi Indonesia. (March 2019) - Dagong, M I A; Baba, S; Rahim, L; Aprilita Bugiwati, S R; Saade, M F; Purnomo, N
Abstract: One of the obstacles in the development of Bali cattle is a common disease such as Jembrana, Brucellosis or Anthrax. Breeding programs for disease resistance are an effort to produce superior livestock resistant to disease. The Major Histocompatibility Complex (MHC) is a group of loci that consists of a collection of important (major) genes that control the immune response. It is known that alleles variations of the MHC genes have a relationship with natural immunity to several diseases in cattle. The aim of this study was to identify the diversity of MHC genes in the Bali cattle population at the Maiwa Breeding Center (MBC). A total of 629 heads of Bali cattle were used as samples in this study. The MHC DRB3 gene was amplified with primers flanking the region of exon 2 using a PCR machine. The product of amplification is 284 bp in lenght. Genotyping and identification of the MHC alleles were carried out by the PCR-RFLP method using P st I restriction enzymes. The results showed that the alleles variation of the MHC gene showed that P allele frequency were 0.856 and 0.938, while the p allele were 0.145 and 0.062 in Barru and Enrekang population, respectively. Observed heterozygosity values obtained in 0.144 showed that the genetic diversity of the MHC genes in the Bali cattle population at MBC was low. The chi-square values (p<0.05) showed that the MHC gene of the Bali cattle at MBC was not in the Hardy Weinberg equilibrium and indicated the possibility of a strong selection of the MHC gene. MHC gene diversity data can be used as one of the references to develope Bali cattle at the MBC.